Aplikasi pasta stroberi sebagai material bleaching terhadap perubahan warna dan kekerasan permukaan enamel - Amelia Hartanto; Devi Rianti; Asti Meizarini (Jurnal Material Kedokteran Gigi, 2012)
Utilization of natural products are very popular in the community lately as a natural substance that is considered more secure, inexpensive, and easy to obtain than chemical. one of which is to use strawberries as an alternative bleaching materials. The purpose of this research is to determine the optimal time of strawberry paste application as bleaching material that has not lowered the enamel surface hardness. Research method contain six sample groups of post extracted incisive teeth after discolorized with black tea in 12 days. Each sample was soaked in 100% strawberry paste in 5 minutes per 8 hours. Soakings were done in 2, 3, 4, 5 weeks. Then, color discoloration observed using Vita shade guide and the enamel surface hardness measured using Vickers hardness tester. Enamel surface hardness data tabulated and then analyzed using Test of Within Subjects, and if there was a difference it followed by t-Test. Enamel discoloration tested using Friedman Test and if there was a difference it followed by Wilcoxon Test. The result: There was a significant difference in color and enamel microhardness of the samples after being soaked in 100% strawberry paste. So it can be concluted that Strawberry paste is effective as a bleaching material without decreasing the surface microhardness after 2 weeks application. Application of strawberry paste in 3 weeks shall decrease the enamel surface microhardness.